Hazards of radiotherapy in patients with cardiac pacemaker: A case report and review of the literature - (:unkn) unknown (My University, 2003)
Modern pacemakers with complementary metaloxide semiconductor (CMOS) circuitry are sensitive to radiation therapy. They may sustain transient or permanent damage depending on the dose, type of radiation, treatment machine and type of the pacemaker. We report a patient who received 6000 cGy with Co60 teletherapy machine to right pectoral muscle location, postoperatively for recurrent soft tissue sarcoma. Radiation dose received by the pacemaker in the left infraclaviculary fossa was measured by thermoluminescent dosimeter (TLD). It was calculated that scatter doses received by the pacemaker was totally 178 cGy. The patient was monitored routinely before, during and after radiotherapy. No sign of abnormal function was seen until his last control, 6 months after radiotherapy. Results of previous reports on hazards of radiotherapy for cardiac pacemakers and recommendations are discussed.
Keywords: Complication; Pacemaker; Radiotherapy